Deviant or wrong? The effects of norm information on the efficacy of punishment - Cristina Bicchieri; Eugen Dimant; Erte Xiao (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2017)
A stream of research examining the effect of punishment on conformity indicates that punishment can backfire and lead to suboptimal social outcomes. In such studies, the enforcement of a behavioral rule to cooperate originates from a single party. This feature may raise concern about the legitimacy of the rule and thereby make it easy for the agents to take a penalty and excuse their selfish behavior. We address the question of punishment legitimacy in our experiment by shedding light upon the importance of social norms and their interplay with punishment mechanisms. We show that the separate enforcement mechanisms of punishment and norms cannot achieve higher cooperation rates. In fact, conformity is significantly increased only in those cases when social norms and punishment are combined, but only when cooperation is cheap. Interestingly, when cooperation is expensive we find that the combination of punishment and empirical information about others conformity can also have traceable detrimental effects on conformity levels. Our results have important implications for researchers and practitioners alike.
Keywords: C91; D03; D73; H26; 330; Conformity; Experiments; Punishment; Social Norms; Trust Game